PERIYAR E. V. RAMASAMY - THE REVOLUTIONARY SOCIAL REFORMER - D.PADMAVATHY (Indian Streams Research Journal, 2013)
Periyar Ramasamy was known as the Voltaire of South India. He was atheist, social reformer, rationalist, prolific writer, effective speaker and an original thinker. He worked for downtrodden people. He started self-respect movement, Anti-Hindi agitation. He opposed the caste system of India. Thandai Periyar was a crusader for social justice. He was born in an affluent family on 17th September 1879 at Erode in Tamil Nadu State. His father was Venkatappa (Naicker) a rich popular merchant and his mother was Chinathayammal. His school career ended within five years. He entered his father's trade. His parents were deeply religions and they frequently arranged religion discourses with great devotion, even in his early teens Ramasamy displayed a keen rationalistic tendency and ridiculed the pundits who gave the talks by pointing out the contradiction in their statements and also their incredible exaggerating. He married Nagammai, aged 13 he reformed his orthodox wife and sowed rationalistic views in her mind. He became the father of a female child, who expired within five months and thereafter had no children. He undertook “renunciation” of family because of the harsh reprimand of his father. He went first to Vijayawada in Andhra State. Then he proceeded to Hyderabad and Kolkatta